The critical roles of caveolin-1 in lung diseases - Fan, Jiarun; Zheng, Siping; Wang, Maoping; Yuan, Xiaoliang (Frontiers in Pharmacology, 2024)
Caveolin-1 (Cav-1), a structural and functional component in the caveolae, plays a critical role in transcytosis, endocytosis, and signal transduction. Cav-1 has been implicated in the mediation of cellular processes by interacting with a variety of signaling molecules. Cav-1 is widely expressed in the endothelial cells, smooth muscle cells, and fibroblasts in the various organs, including the lungs. The Cav-1-mediated internalization and regulation of signaling molecules participate in the physiological and pathological processes. Particularly, the MAPK, NF-B, TGF /Smad, and eNOS/NO signaling pathways have been involved in the regulatory effects of Cav-1 in lung diseases. The important effects of Cav-1 on the lungs indicate that Cav-1 can be a potential target for the treatment of lung diseases. A Cav-1 scaffolding domain peptide CSP7 targeting Cav-1 has been developed. In this article, we mainly discuss the structure of Cav-1 and its critical roles in lung diseases, such as pneumonia, acute lung injury (ALI), asthma, chronic obstructive pulmonary disease (COPD), pulmonary hypertension, pulmonary fibrosis, and lung cancer.